Microbiological profile and antimicrobial susceptibility of bacteria associated with urinary tract infections in Ukrainian adults - K.S. Barannik; O.V. Ishchenko; R.V. Duka; R.M. Molchanov; D.O. Stepanskyi (Medičnì Perspektivi)
The aim of the study was to analyse the microbial profile of the urinary tract infections (UTIs) due to urolithiases and to study susceptibility to antibiotics in its causative agents. The main method of the research was bacteriological. Antimicrobial susceptibility testing was conducted by serial microdilution assay in accordance with recommendations of the European committee on antimicrobial susceptibility testing (EUCAST). For present study 128 unique urine samples were collected from patients with UTIs associated with urolithiasis. Among all collected specimens, 78% (n=100) gave clinically significant growth. Among all examined participants, 88.9% of women (64/72) and 64.3% of men (36/56) had confirmed UTI; in the study, female/male ratio was 1.4 (χ2=9.76; p<0.05). Microorganisms identified in our study predominantly belonged to Bacteria (93.4%), and yeasts of Candida genus comprised only 6.6%. Among all, 66.1% were representatives of Enterobacterales (n=80), particularly, Escherichia coli (38.0%), Klebsiella oxytoca (15.7%), Klebsiella pneumoniae (2.5%), Enterobacter cloacae (5.8%), Proteus mirabilis (4.1%). Isolates of Pseudomonas aeruginosa comprised 3.3%. Among gram-positive isolates, Staphylococcus spp. (14.1%) and Enterococcus spp. (9.9%) were identified. Regarding female/male distribution, the biggest proportion of gram-positive bacteria were isolated from women, statistically significant results were obtained for sex distribution of S. saprophyticus (p<0.05). Antimicrobial susceptibility of Enterobacterales was variable, and the best results were obtained for carbapenems, novel antibiotics (cefiderocol, ceftolozane-tazobactam and ceftazidime-avibactam), aminoglycosides and tigecycline. There were 9 isolates with production of carbapenemases and resistant to all relevant β-lactam antibiotics. All isolated Staphylococcus spp. were β-lactamase producers, one isolate of S. saprophyticus demonstrated methicillin-resistance. To summarise, there is an ongoing outbreak of multidrug-resistant infections in Ukraine and causative agents of UTIs are among the most important contributors. Availability of data on the local antimicrobial susceptibility profile may guide the informed decision making in etiotropic treatment, therefore, contribute to global efforts in rational drug use and fight the resistance escalation.